2012
DOI: 10.3141/2280-06
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Interaction of Crash Occurrence, Mountainous Freeway Geometry, Real-Time Weather, and Traffic Data

Abstract: This study investigated the effect of the interaction between roadway geometric features and real-time weather and traffic data on the occurrence of crashes on a mountainous freeway. The Bayesian logistic regression technique was used to link a total of 301 crash occurrences on I-70 in Colorado with the space mean speed collected in real time from an automatic vehicle identification (AVI) system and real-time weather and roadway geometry data. The results suggested that the inclusion of roadway geometrics and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
91
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 140 publications
(102 citation statements)
references
References 30 publications
10
91
0
1
Order By: Relevance
“…Ahmed et al (2012) used a Bayesian logistic regression technique to assess crash occurrence with freeway geometry and real time weather and traffic data. They found that crash likelihood could double between the dry and snow seasons, because of the interaction between pavement conditions and steep grades.…”
Section: Previous Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Ahmed et al (2012) used a Bayesian logistic regression technique to assess crash occurrence with freeway geometry and real time weather and traffic data. They found that crash likelihood could double between the dry and snow seasons, because of the interaction between pavement conditions and steep grades.…”
Section: Previous Workmentioning
confidence: 99%
“…For instance, several researchers have assessed the effect of weather elements, i.e., snow fall (Andrey, 2010;Eisenberg and Warner, 2005;Hermans et al, 2006;Khattak and Knapp, 2001), rain fall (Abdel-Aty and Pemmanaboina, 2006;Usman et al, 2012;, wind speed (Jung et al, 2011;Usman et al, 2012), temperature (Bergel et al, 2013;Brijs et al, 2008;El-Basyouny and Kwon, 2012 crash occurrence (Ahmed et al, 2012;Brijs et al, 2008;Usman et al, 2012;, whereas other researchers investigated these effects on crash severity (Andrey, 2010;Bergel et al, 2013;Eisenberg, 2004;El-Basyouny and Kwon, 2012). While the above studies are useful in understanding the effect of adverse weather, it is not always possible to identify suitable countermeasures based on the results of these studies.…”
Section: Introductionmentioning
confidence: 96%
“…With the rapid development of traffic surveillance system and detection technologies, real-time traffic data are not only available on freeways and expressways but also on urban arterials (including road segments and intersections). During the past decade, an increasing number of studies have investigated the crash likelihood on freeways by using real-time traffic and weather data (Oh et al 2001, Lee et al 2003, Abdel-Aty et al 2004, Zheng et al 2010, Ahmed et al 2012a, Xu et al 2013a, Xu et al 2013b, Basso et al 2018, Theofilatos et al 2018. It is worth noting that Theofilatos et al (2018) investigated crash occurrence by utilizing real-time traffic data while considering that the number of crashes is very few, and they could be considered as rare events.…”
Section: Introductionmentioning
confidence: 99%
“…In literature, speed variations have been linked to high risk of accidents on freeways (Zheng et al, 2010;Xu et al, 2013b;Ahmed et al, 2012b;Hassan and Abdel-Aty, 2013). This finding of the Bayesian model suggests that large variations in speed have an influence on PTW accidents in urban roads as well.…”
Section: Resultsmentioning
confidence: 82%
“…It is also noted, that the vast majority of studies exploit data from freeways. Concerning accident likelihood in particular, previous research on this topic suggests that the common risk factors are mainly the variations in traffic conditions (Ahmed et al, 2012a and2012b;Ahmed and Abdel-Aty 2012;Xu et al, 2013a andZheng et al, 2010) and low visibility or adverse weather conditions (Xu et al, 2013a;Ahmed et al, 2012b;Abdel-Aty et al, 2012).…”
Section: Introductionmentioning
confidence: 99%